2018
DOI: 10.1016/j.colsurfb.2017.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Nano hydroxyapatite-blasted titanium surface creates a biointerface able to govern Src-dependent osteoblast metabolism as prerequisite to ECM remodeling

Abstract: Over the last several years, we have focused on the importance of intracellular signaling pathways in dynamically governing the biointerface between pre-osteoblast and surface of biomaterial. Thus, this study investigates the molecular hallmarks involved in the pre-osteoblast relationship with different topography considering Machined (Mc), Dual Acid-Etching (DAE), and nano hydroxyapatite-blasted (nHA) groups. There was substantial differences in topography of titanium surface, considering Atomic Force Microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…On this context, a draw of the molecular network of these findings was necessary, and bioinformatics hypothesizes a strong crosstalk between Shh signaling and IL10 being mediated by Src and mTor proteins. Unsurprisingly, we reported previously elsewhere the involvement of Src in the intracellular signaling in response to nano HA‐blasted titanium surfaces and this reinforces our previous hypothesis. This anti‐inflammatory signal might explain the low profile of RANKL expression by osteoblasts, guaranteeing consequently a low profile of osteoclastogenesis at this stage, as already detailed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On this context, a draw of the molecular network of these findings was necessary, and bioinformatics hypothesizes a strong crosstalk between Shh signaling and IL10 being mediated by Src and mTor proteins. Unsurprisingly, we reported previously elsewhere the involvement of Src in the intracellular signaling in response to nano HA‐blasted titanium surfaces and this reinforces our previous hypothesis. This anti‐inflammatory signal might explain the low profile of RANKL expression by osteoblasts, guaranteeing consequently a low profile of osteoclastogenesis at this stage, as already detailed.…”
Section: Discussionsupporting
confidence: 91%
“…Although nanometric‐scaled structures have important properties considering osseointegration, detailed interfacial interactions with osteogenic cells have not been fully addressed. On this matter, we have previously mapped the cellular phenotype of osteoblast when in response to nano hydroxyapatite‐blasted surfaces (nHA), showing a decisive capacity of the nHA in stimulating osteoblast differentiation by requiring Src as prerequisite . However, in order to better comprehend the molecular mechanisms triggered by nHA, other aspects must be addressed such as inflammatory cytokines reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we have shown that cells actively respond to biomaterials modifying their morphology as an immediate consequence of a well‐orchestrated cytoskeleton rearrangement upon integrin activation, where the phosphorylation of cofilin drives actin filaments rearrangement and governs cell adaptation on the substrate. Additionally, on the adaptive process on the biomaterials, we have also shown that the cell growth requires intracellular cascades requiring MAP kinases (ERK, JNK, and P38) and ECM remodeling . In turn, ECM plays structural and functional roles, it being sufficient and necessary for the plasticity of the cells and their remodeling to be considered in regenerative mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…Among the biomaterials, those devoted to bioengineering protocols need to recapitulate the wound‐healing steps triggering a moderate inflammatory cascade activating hemostasis and later requiring platelets and fibrinogen. In this context, advances in physics and chemistry area allowed the application of nanoscaled structures on modifying and functionalizing molecules/materials, ameliorating their performance in medical proposes . It is not new the purpose of layered double hydroxides (LDHs) as biomaterial .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation